2015
DOI: 10.1097/nen.0000000000000197
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in the Tricarboxylic Acid Cycle in Huntington Disease and in a Huntington Disease Mouse Model

Abstract: Glucose metabolism is reduced in the brains of patients with Huntington disease (HD). The mechanisms underlying this deficit, its link to the pathology of the disease and the vulnerability of the striatum in HD remain unknown. Abnormalities in some of the key mitochondrial enzymes involved in glucose metabolism, including the pyruvate dehydrogenase complex (PDHC) and the tricarboxylic acid (TCA) cycle, may contribute to these deficits. Here, activities for these enzymes and select protein levels were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 34 publications
5
26
1
Order By: Relevance
“…For example, the liver clock promotes gluconeogenesis and glycogenolysis during the sleep/fasting period, while fostering glycogen and cholesterol synthesis during the wake/feeding period. The CBT measures suggest that the circadian regulation of metabolism is compromised in the Q175 line and fits with prior work that demonstrated that HD patients as well as the Q175 mice have deficits in the tricarboxylic acid cycle (Naseri et al, ) responsible for the production of ATP. The diurnal variation in CBT was also attenuated in the R6/2 (Fisher et al, ) and BACHD mice (Kudo et al, ).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…For example, the liver clock promotes gluconeogenesis and glycogenolysis during the sleep/fasting period, while fostering glycogen and cholesterol synthesis during the wake/feeding period. The CBT measures suggest that the circadian regulation of metabolism is compromised in the Q175 line and fits with prior work that demonstrated that HD patients as well as the Q175 mice have deficits in the tricarboxylic acid cycle (Naseri et al, ) responsible for the production of ATP. The diurnal variation in CBT was also attenuated in the R6/2 (Fisher et al, ) and BACHD mice (Kudo et al, ).…”
Section: Resultssupporting
confidence: 84%
“…Like the Q175 mutants, the R6/2 mice also exhibited episodes of hypothermia, particularly evident in the dark period. Overall, there is strong evidence for mitochondrial dysfunction in HD as well as in other neurodegenerative diseases (Carmo, Naia, Lopes, & Rego, ; Dubinsky, ; Franco‐Iborra, Vila, & Perier, ; Kuhl et al, ; Naseri et al, ). Unintended weight loss is a hallmark of HD patients and a recent study found that a high body mass index (BMI) is associated with a significantly slower rate of functional, motor, and cognitive deterioration (van der Burg et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…63 In addition, we also found that a subunit of complex II (succinate dehydrogenase), SDHA, subunits of complex III (cytochrome bc 1), UQCRC1 and 2, and a component of cytochrome c oxidase, SCO2 (complex IV), were also less abundant in HD cortex relative to controls. Overall, the observed changes in the protein levels in HD brains are consistent with the current view of the mechanisms of mitochondrial dysfunction in HD, such as a decrease in the enzymes of pyruvate dehydrogenase complex (PDHC), 64 inhibition of the respiratory chain enzymes (described above), increased oxidative stress 65 (superoxide dismutase 1, SOD1, is increased), decrease in brain-specific creatine kinase (CKB), 66 and inhibition of mitochondrial protein import by mutant Htt 67 (TIMM44 and TIMM8A, components of presequence translocase-associated motor complex, PAM, are decreased). The observed changes in six family members of the motor protein kinesin and dynein and changes in abundance of mitochondrial fission factors MFF, MFN2, and FIS1 are also consistent with the idea that mutant Htt may dysregulate mitochondrial dynamics and trafficking.…”
Section: Discussionsupporting
confidence: 86%
“…Several evidence reports that any alteration in mitochondrial activity propels the pathogenesis of HD; for instance, mtDNA damage and deletion have been reported in HD brains [53]. Significant defects in the enzymes associated with mitochondrial respiratory chain and glucose metabolism, including pyruvate dehydrogenase complex (PDHC), aconitase and succinate dehydrogenase (SDH) have been reported in HD patients [54]. Furthermore, SDH inhibitions by malonate and 3-nitropropionic acid have also reported to cause excessive mitochondrial fission and neuronal death associated with clinical and pathological features of HD [55].…”
Section: Huntington's Diseasementioning
confidence: 98%